2014
DOI: 10.1111/jphp.12291
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of saponins extract fromPanax japonicuson myocardial infarction: involvement of NF-κB, Sirt1 and mitogen-activated protein kinase signalling pathways and inhibition of inflammation

Abstract: The studies demonstrated that SPJ exerted beneficially cardioprotective effects on MI rats, mainly inhibiting NF-κB, ERK1/2 and p38 MAPK activation, but increased the expression of SIRT1, alleviating MI injury and cardiac cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 45 publications
(88 reference statements)
1
16
0
Order By: Relevance
“…It has been known that MAPK signaling pathways play critical roles in the regulation of inflammatory mediators [34,35]. Especially, ERK1/2 and p38 MAPK signaling pathways serve as main signaling pathways in inflammatory response [18,19]. It has been reported that stimulating of RAW264.7 by LPS induces phosphorylation and activation of ERK1/2 and p38 MAPKs [11,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known that MAPK signaling pathways play critical roles in the regulation of inflammatory mediators [34,35]. Especially, ERK1/2 and p38 MAPK signaling pathways serve as main signaling pathways in inflammatory response [18,19]. It has been reported that stimulating of RAW264.7 by LPS induces phosphorylation and activation of ERK1/2 and p38 MAPKs [11,36].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MAPK is involved in the regulation of inflammatory mediator production, especially P-ERK1/2 and P-P38 MAPK activities [18,19]. Thus, the effect of HP on P-ERK1/2 and P-P38 expression in vivo and in vitro was investigated.…”
Section: Hp Suppresses P-erk1/2 and P-p38 Expression In Vivo And In Vmentioning
confidence: 99%
“…However, the clinical application of MSC transplantation is restricted by low survival rates of MSCs following transplantation (6). Several signaling pathways are abnormally regulated in the process of MI, including transforming growth factor-β (TGF-β)/small mothers against decapentaplegic, Janus kinase-signal transducers and activators of transcription, p38 mitogen-activated protein kinases (p38MAPK), phosphoinositide-3-kinase (PI3K)/Akt-endothelial nitric oxide synthase, PI3K/protein kinase C and Wnt (7)(8)(9). Among these signaling pathways, p38MAPK is involved in regulating the inflammatory process.…”
Section: Introductionmentioning
confidence: 99%
“…This study also showed that the benefit could be enhanced with coadministration of extracts of the Safflower plant (Cartharmus tinctorius L) thus suggesting that combination therapy could effectively enhance the cardioprotective effect of ginseng-related compounds. Furthermore, seven-day pretreatment with a saponin extract from P japonicas exerted substantial protection in rats subjected to 12 hours of coronary artery ligation, without reperfusion, as manifested by improved function, reduced injury including apoptosis as well as reduced markers of oxidative stress and expression levels of cytokines (He et al 2012;Wei et al 2014).…”
Section: R a F Tmentioning
confidence: 98%